Application of SiO2 Nanoparticles as Lubricant Additive in VCRS: An Experimental Investigation - Desai, Nilesh S.; Patil, P. R. (Asian Review of Mechanical Engineering, 2015)
In this work, the SiO2 nano-oil is proposed as a promising lubricant to enhance the performance of vapour compression refrigerator compressor. The stability of SiO2 nanoparticles in the oil is investigated experimentally. It was confirmed that the nanoparticles steadily suspended in the mineral oil at a stationary condition for long period of time. The application of the nano-oil with specific concentrations of 1%, 2% and 2.5 %( by mass fraction) were added in the compressor oil. The VCRS performance with the nanoparticles was then investigated using energy consumption tests. The result shows the COP of system were improved by 7.61%, 14.05% & 11.90%, respectively, when the nano-oil was used instead of pure oil.